Social interactions and unemployment - Peter Hedström; Ann-Sofie Kolm; Yvonne Åberg (Institute for Labour Market Policy Evaluation (IFAU), 2003)
This paper is concerned with social interactions and their importance for unemployment. A theoretical model is specified in which the psychological costs of unemployment depend upon the unemployment level. The analysis reveals social multiplier effects, and shows that multiple unemployment equilibria may emerge. Data on all 20- to 24-year-olds living in Stockholm during the 1990s are used to test hypotheses from the model. The results show that individuals transition rates out of unemployment is strongly influenced by the unemployment level within their neighborhoods.
Keywords: J64; Z13; 330; Social interactions; social norms; social multipliers; unemployment